SISTEM INFORMASI OPTIK MILALA BERBASIS WEB - Dwita Putri Br Pandia (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
At this time the increase in the use of technology is getting higher, no wonder if we findthat some of the other companies are already using computer technology on the systemsin the company. Milala Optical Store is one of the Companies engaged in Glasses Saleswhich still uses manual systems in the glasses sales process so that the length ofrecording data in the sales process of glasses sometimes makes consumers have to waitlong. The current system is still done manually, starting from recording consumers whobuy goods, to storing other data related to the sales process, so that it is possible duringthe process there is an error in recording, inaccurate reports and delays in searches.data needed. This study aims to produce an optical information system development atthe Milala Optical Shop. Development of this system is made with PHP and MySQLprogramming languages.